Reversible computation : 12th International Conference, RC 2020, Oslo, Norway, July 9-10, 2020, Proceedings /: 12th International Conference, RC 2020, Oslo, Norway, July 9-10, 2020, Proceedings. (2020) - Unknown
No abstract available